2022
DOI: 10.3389/fnut.2022.846873
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Therapy With VSL#3® in Patients With NAFLD: A Randomized Clinical Trial

Abstract: AimTo evaluate if VSL#3® [a high-concentration multi-strain probiotic mix containing one strain of Streptococcus thermophilus BT01, three strains of Bifidobacteria (B. breve BB02; B. animalis subspecies [subsp.] lactis BL03, previously identified as B. longum BL03; and B. animalis subsp. lactis BI04, previously identified as B. infantis BI04), and four strains of Lactobacilli (L. acidophilus BA05, L. plantarum BP06, L. paracasei BP07, and L. helveticus BD08, previously identified as L. delbrueckii subsp. bulga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In addition, a randomized controlled study revealed that patients with NAFLD treated daily with Lactobacillus and Bifidobacterium species showed decreased levels of ALT and γGT, decreased counts of CD4+ T-cells and CD8+ T-cells, and improved HS fibrosis (87). Chong et al (88) and Derosa et al (89) found that NAFLD patients treated with VSL#3 R had a decreased AST/ALT ratio and hs-CRP level and improved IR and endothelial dysfunction. In addition, patients with NAFLD supplemented with metformin and probiotics showed improved serum AST and ALT levels and ultrasound grading of NASH (90).…”
Section: Craven Et Al (1)mentioning
confidence: 99%
“…In addition, a randomized controlled study revealed that patients with NAFLD treated daily with Lactobacillus and Bifidobacterium species showed decreased levels of ALT and γGT, decreased counts of CD4+ T-cells and CD8+ T-cells, and improved HS fibrosis (87). Chong et al (88) and Derosa et al (89) found that NAFLD patients treated with VSL#3 R had a decreased AST/ALT ratio and hs-CRP level and improved IR and endothelial dysfunction. In addition, patients with NAFLD supplemented with metformin and probiotics showed improved serum AST and ALT levels and ultrasound grading of NASH (90).…”
Section: Craven Et Al (1)mentioning
confidence: 99%
“…97,98 A randomized trial including 60 NAFLD patients reported a significant reduction in triglycerides, transaminases, and gamma-glutamyltransferase, but no change in fasting plasma glucose, total cholesterol, low-density lipoprotein-cholesterol and highdensity lipoprotein-cholesterol with VSL#3 compared with controls. 99 The evidence suggests probiotics and prebiotics have a possible benefit in NAFLD, high-quality studies are still limited.…”
Section: Role Of the Intestinal Microbial Barrier In Nafld Developmentmentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled clinical trial showed that multistrain probiotic supplementation can decrease insulin, insulin resistance, TNFα, and IL-6 in patients with NAFLD [ 178 ]; further, in the same line, treatment with Lactobacillus bulgaricus and Streptococcus thermophilus can decrease ALT and AST activity, and gamma glutamyl transferase (GGT) levels in NAFLD patients [ 179 ]. Another randomized, double-blind, placebo-controlled clinical trial reports that administration of VSL#3 decreased triglycerides and high-sensitivity C-reactive protein levels, as well as transaminases and GGT activity [ 180 ]. Interestingly, Shavakhi et al demonstrated that treatment with Metformin plus Protexin ( L. acidophilus , L. casei , L. rhamnosus , L. bulgaricus , B. breve , B. longum , Streptococcus thermophilus ) decreases ALT and AST activity, better than Metformin alone in patients with NASH [ 181 ].…”
Section: Probioticsmentioning
confidence: 99%